2020
DOI: 10.1021/acsomega.0c01454
|View full text |Cite
|
Sign up to set email alerts
|

Probing the 14-3-3 Isoform-Specificity Profile of Protein–Protein Interactions Stabilized by Fusicoccin A

Abstract: Fusicoccin A (FC) is a fungal phytotoxin that stabilizes protein–protein interactions (PPIs) between 14-3-3 adapter proteins and their phosphoprotein interaction partners. Recently, FC has emerged as an important chemical probe of human 14-3-3 PPIs involved in cancer and neurobiology. These previous studies have established the structural requirements for FC-induced stabilization of 14-3-3·client phosphoprotein complexes; however, the effect of 14-3-3 isoforms on FC activity remains underexplored. This is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Ser166 and Ser186 on hDM2 are involved in apoptosis, signalling pathway regulation and ubiquitination. protein are clear between the isoforms [36,37]. The 14-3-3 proteins exist as homo or heterodimers where each monomer consists of nine α-helices forming an amphipathic binding groove.…”
Section: Nls Elsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ser166 and Ser186 on hDM2 are involved in apoptosis, signalling pathway regulation and ubiquitination. protein are clear between the isoforms [36,37]. The 14-3-3 proteins exist as homo or heterodimers where each monomer consists of nine α-helices forming an amphipathic binding groove.…”
Section: Nls Elsmentioning
confidence: 99%
“…protein are clear between the isoforms [36,37]. The 14-3-3 proteins exist as homo or heterodimers where each monomer consists of nine α-helices forming an amphipathic binding groove.…”
Section: Nls Elsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lentini Santo et al [148] reported that the FC derivatives called FC-H and 16-O-Me FC-H (Figure 11), lacking substitutions in the C ring, stabilized the interaction between the N-terminal non canonical mode III motif, whereas FC, FC-J, and FC-THF which carry substituents at the C ring were ineffective, due to steric hindrance with the Gln residue of the peptide within the binding groove. Finally, in a study aimed to assess 14-3-3 isoform specificity of FC association to mode III targets, Sengupta et al [149] tested the binding of different recombinant human 14-3-3 isoforms to phosphorylated hexapeptides containing known mode III motifs. Despite that isoform-dependent interactions were displayed better in the absence of FC, the stabilization by FC of the association of the 14-3-3σ isoform was apparently sensitive to the type of client peptide.…”
Section: Fc Derivatives For Pharmacological Applicationsmentioning
confidence: 99%
“…Even though sequence conservation between the isoforms can indicate redundancy in protein function, this is not the case for 14-3-3 proteins as different affinities towards a target protein are clear between the isoforms. [35][36] 14-3-3 proteins exist as homo or heterodimers where each monomer consists of nine α-helices forming an amphipathic binding groove. Four α-helices are directly responsible for dimer formation, while the rest of the α-helices form the "W" shape of the protein dimer.…”
Section: Introductionmentioning
confidence: 99%